Federally Administered Tribal Areas (FATA) Reforms Unveiled: A Case Study of Tehsil Khar, District Bajaur, Khyber Pakhtunkhwa - Zeb, Burhan; Nawab, Habib Ullah (Annals of Human and Social Sciences, 2023)
This research paper provides a thorough examination of the knowledge and perspectives surrounding the shift from the Frontier Crimes Regulation (FCR) to the current reforms in the Federally Administered Tribal Areas (FATA), with a specific focus on Tehsil Khar in District Bajaur, Khyber Pakhtunkhwa. By integrating qualitative insights with quantitative data, the study presents a comprehensive analysis of the community’s perceptions regarding these reforms and their potential impact on the political, societal, and gender domains. This study examines the ambitions, concerns, and recommendations of the population, providing insight into the changing socio-political dynamics in the region. The study revealed several significant findings. Firstly, there exists a prevailing feeling that strongly opposes the repressive characteristics associated with the FCR system. Secondly, the transition from the FCR system to a reformed framework is met with a sense of optimism. Despite the existence of worries over the potential delay in implementing the changes, they are generally regarded in a good light for their transformative effect on the political landscape. A majority of individuals concur on the beneficial outcomes associated with these reforms. The primary suggestions for promoting successful and significant transformations in the FATA encompass the complete elimination of the FCR and the enhancement of legal structures; the implementation of educational workshops and awareness initiatives to enlighten the indigenous populace about the constitution of Pakistan and conventional legal systems; and the comprehensive restructuring of bureaucratic mentalities and establishments through substantial reforms.